2019
DOI: 10.1007/s00044-019-02384-8
|View full text |Cite
|
Sign up to set email alerts
|

Different reactivity to glutathione but similar tumor cell toxicity of chalcones and their quinolinone analogues

Abstract: Non-enzyme catalyzed nucleophilic addition of reduced glutathione (GSH) onto two open-chain sulfonamide chalcones and two quinolinone-chalcone hybrids were studied to investigate the relationship between tumor cell cytotoxic activities and GSH-reactivities of the compounds. The consumption of the chalcones or the quinolinone-chalcone hybrids due to conjugation with GSH was evaluated by analytical high-performance liquid chromatography, and the formed diastereomeric adducts were identified by liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Since the 4-methoxy substitution can more effectively increase the electron density on the carbon–carbon double bond, and the formed chalcone is resonance stabilized, the elimination process is more effective in the case of 2 than 1 . Similar conclusions were made by d’Oliveira et al while investigating a few chalcones and their rigid quinolone analogues [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…Since the 4-methoxy substitution can more effectively increase the electron density on the carbon–carbon double bond, and the formed chalcone is resonance stabilized, the elimination process is more effective in the case of 2 than 1 . Similar conclusions were made by d’Oliveira et al while investigating a few chalcones and their rigid quinolone analogues [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…A number of synthetic routes have been reported for synthesis of the o / m / p -(sulfonamido)chalcones and their general synthesis involves the Claisen-Schmidt aldol condensation of o / m / p -sulfonamidoacetophenone precursors with benzaldehyde derivatives in the presence of an acid [ 20 ] or base [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 21 , 22 , 23 , 24 , 25 ] followed by spontaneous in situ dehydration of the incipient β-hydroxyketone intermediates. The sulfonamidoacetophenones 2 are, in turn, prepared from the corresponsing o / m / p -aminoacetophenones 1 with alkyl/arylsulfonyl chloride derivatives in the presence of an amine as a base in the absence or presence of a solvent ( Scheme 1 ).…”
Section: Synthesis Of O / M / P -(Sulfonamido)chalconesmentioning
confidence: 99%
“…These analytical techniques revealed that the conjugated carbon scaffolds of o / m / p -aminochalcones and their sulfonamide derivatives are essentially planar. However, twisting of the sulfonamide moiety from coplanarity of the conjugated carbon framework is commonly observed in the crystal structures of the ortho - [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], meta - [ 22 , 23 ] and para -sulfonamido appended chalcones [ 24 , 33 ]. The twisting of the sulfonamide moiety from coplanarity of the conjugated carbon framework has also been observed in the crystal structures of the analogous N -(2-acetyl-4-(styryl)phenyl)sulfonamides [ 34 ] and the corresponding 5-styryl-2-sulfonamidochalcone hybrids [ 26 ].…”
Section: Structural Properties Of O / M / P -(Sulfonamido)chalcone Derivativesmentioning
confidence: 99%
See 2 more Smart Citations